Kindness in memorable university teachers - Porta, Luis Gabriel; Flores, Graciela Nelida (Revista de Estudios y Experiencias en Educación, 2017)
ABSTRACT. The article presents some insights derived from research on ‘good teaching practices’ in the context of the School of Humanities, Mar del Plata State University, Argentina. He professor in charge of the ‘Introduction to Philosophy’ course has been signaled as ‘memorable’ by her advanced students, and thus become part of the investigation. In her classes, the relationship with the students entails peculiar ethical dimensions, and hospitality is one of the categories involved in her didactic proposal. Much data has been gathered through ethnographic reports of classwork, interviews, surveys and analysis of reference materials, which aims at throwing light into good teaching at university, as part of the investigation conducted by the Research Team on Education and Cultural Studies (GIEEC) in this University.KEY WORDS. Hospitality – Pedagogic Bond – Memorable Professors – Higher Education Didactics.doi:10.21703/rexe.201730334812